2012
DOI: 10.1590/s1516-05722012000400019
|View full text |Cite
|
Sign up to set email alerts
|

Clinical applicability of natural product(s)-containing mouthwashes as adjunctive treatment of biofilm-induced gingivitis: a systematic review

Abstract: RESUMO: Aplicabilidade clínica de colutórios à base de produtos naturais como tratamento adjuvante da gengivite induzida por biofilme: uma revisão sistemática. Os produtos naturais têm surgido como alternativa eficaz e de baixo custo para o tratamento de várias doenças da cavidade oral. Objetivou-se avaliar, a partir de revisão sistemática da literatura, se há evidências científicas garantindo a utilização segura e eficaz de antissépticos bucais contendo produto(s) natural(is) como tratamento adjuvante da geng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…According to our analysis, the mouthwash of thymol- and carvacrol-rich L. sidoides EO (ethanol-free) rinsed twice a day is an effective agent to prevent/disrupt the accumulation of cariogenic biofilm [ 36 ]. Furthermore, in a previous systematic review [ 76 ] we also found that such experimental mouthwash was effective against biofilm-induced gingivitis in adults. Altogether, these findings highlight the therapeutic potential of L. sidoides EO for dental care, but it is important to note that further studies are needed to investigate its effects on other aspects related to tooth decay, such as bacterial acid production, biofilm formation, enamel de- and remineralization, inhibition of glycosyltransferase production/activity, among others.…”
Section: Discussionmentioning
confidence: 67%
“…According to our analysis, the mouthwash of thymol- and carvacrol-rich L. sidoides EO (ethanol-free) rinsed twice a day is an effective agent to prevent/disrupt the accumulation of cariogenic biofilm [ 36 ]. Furthermore, in a previous systematic review [ 76 ] we also found that such experimental mouthwash was effective against biofilm-induced gingivitis in adults. Altogether, these findings highlight the therapeutic potential of L. sidoides EO for dental care, but it is important to note that further studies are needed to investigate its effects on other aspects related to tooth decay, such as bacterial acid production, biofilm formation, enamel de- and remineralization, inhibition of glycosyltransferase production/activity, among others.…”
Section: Discussionmentioning
confidence: 67%
“…However, side effects like mucosal irritation, burning sensation and altered taste perception have been reported with short‐term (1 week) usage of non‐alcohol‐based 0.2% chlorhexidine mouthrinse . Thus, there exists a need for safer and cheaper alternatives to existing mouthrinses (especially chlorhexidine) with equivalent antimicrobial action and potency . In this regard, the natural compounds (plant extracts) containing/herbal mouthrinses have been suggested as probable alternatives based on encouraging results from various clinical trials .…”
Section: Discussionmentioning
confidence: 99%
“…Apart from the chemical agents containing mouthrinses (bisguanide antiseptics, phenolic antiseptics, quaternary ammonium compounds, hexetidine, povidone iodine, triclosan, delmopinol, salifluor, metal ions, and oxygenating agents), natural compounds (plant extracts) containing/herbal mouthrinses such as sanguinarine and propolis are commercially available and have been evaluated in clinical trials for controlling plaque and gingivitis . In recent years, numerous natural compounds containing mouthrinses have been introduced in dentistry and are being claimed to be efficacious in plaque and gingivitis control . Of various plant extracts used as a base for mouthrinses, Azadirachta indica (neem), a medicinal herb native of India and naturalized in most of the tropical and subtropical countries, deserves a special mention as it has been used as a chewing stick for maintaining oral hygiene in traditional Indian medicine .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations